2019
DOI: 10.1002/cam4.2370
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic validity of the European Neuroendocrine Tumor Society (ENETS) and American Joint Committee on Cancer (AJCC) 8th staging systems in colonic neuroendocrine neoplasms

Abstract: Purpose This study aimed to investigate the characteristics of colonic neuroendocrine neoplasms (NENs) and to validate the prognostic value of the European Neuroendocrine Tumor Society (ENETS) and American Joint Committee on Cancer (AJCC) 8th staging systems. Methods A total of 167 and 1248 patients with colonic NENs from 12 medical centers across China and from the Surveillance, Epidemiology, and End Results (SEER) cancer registry in the United States, respectively, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…Surgical treatment is always recommended for patients with PNETs with or without distant metastasis. Similar to pancreatic ductal adenocarcinoma [17], patients with tumors located in the tail or body of the pancreas have a more favorable outcome. Although several studies have demonstrated that nomograms could be ideal statistical prediction models for PNETs [18,19,20], our updated nomograms were established with more detailed clinical information after excluding indeterminacy parameters from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is always recommended for patients with PNETs with or without distant metastasis. Similar to pancreatic ductal adenocarcinoma [17], patients with tumors located in the tail or body of the pancreas have a more favorable outcome. Although several studies have demonstrated that nomograms could be ideal statistical prediction models for PNETs [18,19,20], our updated nomograms were established with more detailed clinical information after excluding indeterminacy parameters from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery treatment always was recommend for PNETs patients with or without distant metastasis. As similar to pancreatic ductal adenocarcinoma [17], the patient whose tumor located in tail or body of pancreas has more favorable outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Однако авторы указывают на необходимость тщательного отбора пациентов с учетом определенных критериев. Все предложенные критерии (Mayo Clinic, UWO, ENETS) подразумевают обязательное удаление первичного очага (индекс Ki-67 менее 2%), отсутствие внепеченоч-ных метастазов и стабилизацию процесса на фоне проводимой терапии в течение не менее 6-12 мес [4]. Таким образом, ТП можно рассматривать как единственный радикальный метод лечения этой категории пациентов [3,4,9].…”
Section: Case Reportsunclassified
“…Лечение больных с нерезектабельными метастазами нейроэндокринного рака является серьезным вызовом онкологам и хирургам во всем мире [1,2]. Низкий потенциал злокачественности некоторых нейроэндокринных опухолей позволяет рассматривать трансплантацию печени (ТП) как единственный радикальный метод лечения данной категории больных [3,4]. В ведущих клиниках США и ЕС разработаны и успешно приме-няются критерии ТП больным с нерезектабельными метастазами нейроэндокринного рака [5,6].…”
Section: Introductionunclassified